Effects of the Use Knee-Ankle-Foot Orthosis on Proprioception Function Change in Healthy Adult Male - Nuralam Sam1, Andriati1, Noor Idha Handajani1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Proprioception includes joint position and motion. Sensory information, central processes, and neuromuscular control are important in improving joint stability. The effective use of knee joint orthosis on knee joint performance, balance and coordination is still highly controversial and has slight information on the effect of the orthotic use on proprioceptive function. Objective: To analyze the effect of knee orthosis on proprioception function in adult male health’s subjects. Method: This study used an experimental research with pre-post study design. The sample of this study was the male patient of Physical and Rehabilitation treatment that met inclusion criteria. The data was taken by consecutive sampling in February 2017. The subjects were 11 healthy male adults who aged of 21-40 years old that meeting the inclusion criteria. All the subjects were measured proprioception function before and at 30 minutes using knee orthosis. Joint position sense (JPS) and time to detect passive movement (TTDPM), were measured by the cybex isokinetic dynamometer tool to measure the function of proprioception. Result: All the mean values of JPS before and at 30 minutes by using orthosis on both sides did not statistically show a significant difference (p >0.05), except at the corner of the JPS 60° on the right-sided knee (p <0.05). It meant TTDPM before and during 30 minutes using orthosis on both sides of the knee also did not show a significant difference (p >0.05). Conclusion: The use of ambulatory knee-ankle-foot orthosis caused the change in proprioception (JPS) at the right side 60o knee angle on the subject before and at 30 minutes using knee orthosis.